Transformasi Digital Akuntansi UMKM Kuliner melalui Cloud Accounting di Kecamatan Oebobo - Rivany Fabiola Nahak Abrantes; Maria Goreti Malut; Adiutrix Maria Irayanti Seran (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the readiness level of culinary Micro, Small, and Medium Enterprises in Oebobo District, Kupang City, to adopt Cloud Accounting as part of digital accounting transformation. This study employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation involving 13 culinary MSMEs. The analysis was based on four main indicators: technology, human resources, finance, and environment. The findings show that MSMEs’ readiness in terms of technology and finance is relatively adequate, as indicated by the use of digital devices, cashier applications, QRIS, and the ability to finance certain digital systems. However, the human resources and environmental aspects still need to be strengthened due to low digital accounting literacy, uneven understanding of Cloud Accounting, the perception of cost as an additional burden, and limited socialization and assistance from the government or related institutions. This study concludes that the adoption of Cloud Accounting among culinary MSMEs requires continuous training, user-friendly systems, affordable costs, and a stronger digital ecosystem.